Spatial patterns of mortality in northern Finland in 1961-1980 - Näyhä, Simo, 1942- (Acta Universitatis Ouluensis. Series D, Medica., 1986)
Examines mortality in Northern Finland (provinces of Oulu and Lapland) for temporal trends for the period 1961-1980 and for epidemological patterns in medical geography, morbidity, mortality and cause of death, and consequent variations by commune (settlement) for the period 1961-1978. Includes tables, maps and charts.